Lifestyle of school going adolescents in Mumbai, India: a cross sectional study - Patil, Shalaka P.; Almale, Balaji (International Journal of Contemporary Pediatrics, 2018)
Background: Adolescents, as defined by World Health organization, constitute individuals in between the age group of 10 to 19 years. Children, youth and young people are the other groups which have ages which overlap with the adolescent age group. The hormonal changes at this age are responsible not only for physiological growth but also emotional and cognitive changes. Lifestyle in this age group may have lasting and, in many cases, lifelong implications. We conducted this cross-sectional study to holistically analyse lifestyle of school adolescents in Mumbai. Methods: This was a cross sectional study conducted in the in a tertiary care medical college. The students belonging to an English medium co-education school of a metropolitan city were included in this study on the basis of a predefined inclusion and exclusion criteria. A culturally acceptable questionnaire was structured in simple language and used in this study. Demographic data was asked. All questions were closed ended and requiring specific response the questionnaire was subjected to critical evaluation by experts from the field of Public Health Pediatrics, high school teachers, heads of schools, experts from Social justice and law input from the experts were incorporated in the questionnaire. Statistical analysis was done using SSPE 22.0 Software. Results: A total of 538 adolescents were studied in this cross-sectional study. There were 270 boys (50.18%) and 268 (49.82%) girls with a M:F ratio of 1:0.95. Mean age of the studied cases was found to be 12.4±1.44 years. Majority of the adolescents were found to be residing in buildings (66.36%) and average family size was found to be 5.63±3.34 members Majority of the boys and girls (66.92%) were not having any knowledge about HIV/AIDS.7.06% adolescents were found to have suicidal or homicidal thoughts. 93.31% adolescents liked to come to school and 83.83% claimed to be obedient. Conclusions: This cross-sectional study highlights the fact that adolescents have a significant amount of psychosocial problems. Important amongst these included inclination towards substance abuse, suicidal or homicidal thoughts and ignorance about HIV/AIDS. Strategies to tackle these issue needs to be devised so as to tackle these problems faced by adolescents.